Utilization of E-Learning as an Internet-Based Learning Medium - Didik Himmawan; Elfira Ade Lita; Ilmatuz Zahro; Nisaul Isti’ani; Kholifatun Nazilah (Journal Of Psychology, Counseling And Education, 2026)
The development of information technology in the Industrial 4.0 era has transformed the educational paradigm through the utilization of the internet as the primary learning infrastructure. This research aims to analyze the utilization of e-learning as an internet-based learning medium and explore its effectiveness in the modern educational process. The research method used is descriptive qualitative with a literature review approach, by collecting and synthesizing relevant literature from various reliable scientific sources. The results indicate that e-learning provides accessibility flexibility, time efficiency, and enriches interaction through various multimedia features that are responsive to the needs of students in the digital era. Although it offers great potential, its implementation still faces technical challenges and the need for pedagogical adaptation. This study concludes that combining interactive digital content with stable platforms is the key to successful technology-based educational transformation.